Frequency of Refractive Error in Children of District Abbottabad (Medical Forum Monthly, 2024)
Objectives: To investigate the prevalence of refractive errors in children. Design and Place of Study: A descriptive case series study of 10,000 patients conducted in the department of ophthalmology Shahina Jamil Teaching Hospital Frontier Medical College Abbottabad. 10-15 years old children of district Abbottabad were initially screened. Children identified to have visual acuity equal to or less then 6/12 underwent refraction with autorefractor (with cycloplegic where needed) and were prescribed glasses. Duration of Study: From 2008-2009. Outcome Measure: Proportion of children with Myopia, Hpermetropia and Astigmatism. Results: A total of 10,000 children were screened.4.7 % of the total children screened had impaired visual acuity while 4.35% were found to have refractive errors. Prevalence of refractive error was found slightly more common among females. Myopia was found to be three times more common 3.33% than hypermetropia (1.00%) overall prevalence of astigmatism was found to be (1.78 %). Conclusion: Refractive errors are significant cause of visual disability in children. Medical staff can effectively identify those children with poor vision for refraction and spectacles.